Farmyard Manure Integrated with Triple Superphosphate for Improved Soil Conditions and Yield of Bio-Fortified Common Beans - Wabusa, Derrick; Masinde, Margaret Namugwanga; Opio, Julius (East African Nature and Science Organization, 2024)
Increasing prices of fertilizers and low nutrient concentration in organic manure are highly contributing to poor soil conditions and increased yield gap of bio-fortified common beans.  A field study was carried out to assess the effect of farmyard manure integrated with triple superphosphate on soil conditions and yield of bio-fortified common bean Genotypes in central Uganda. The experiments were set in a Randomized Complete Block Design (RCBD) conducted at Mukono Zonal Agricultural Research Institute (MUZARDI) in two rainfall seasons. Treatments included; Cattle manure + TSP, Swine manure + TSP, Chicken manure + TSP, TSP alone and control replicated five times. Bio-fortified common bean genotypes studied were: Naro bean 1, Naro bean 3 and NABE16 a local check. Data was collected on; organic matter, soil pH, nitrogen, potassium and phosphorus content, harvest index, number of pods, pod length, number of seeds per pod, weight of 100 seeds, and grain yield of bio-fortified common beans. Data was subjected to statistical test and analysis of variance using GenStat statistical package (15th edition). Results showed that amending field plots with Swine manure + TSP significantly increased Organic matter by; 1.51% and potassium 1.22% than Chicken manure + TSP, Cattle + TSP, TSP alone and a control respectively. Chicken manure + TSP increased soil pH and Nitrogen by 1.80 and 2.20% while, TSP alone improved Phosphorus by 5.2 PPM than other treatments. Yield parameters were not significantly (P>0.05) affected by treatments except weight of 100 seeds. However, bean genotypes grown in Swine manure + TSP recorded maximum yield of 14 pods, 4 seeds per pod, 32.93 g weight of 100seeds, grain yield was (1843 kgha-1) and lowest (1253 to 650 kg/ha) in TSP+ cattle manure and control. It was therefore, concluded that swine manure + TSP significantly improved soil conditions and yield of bio-fortified common beans. Therefore, basing on these findings, farmers should adopt amendment of swine manure with TSP for improved soil conditions and yields of Naro bean